Impact of COVID-19 on Intensive Care Unit Nurse Duty of Care and Professional Roles: A Qualitative Content Analysis - Jacqueline Christianson MSN, RN, FNP-C; Jill Guttormson PhD, RN; Natalie Susan McAndrew PhD, RN, ACNS-BC; Kelly Calkins PhD, RN (SAGE Publishing, 2022)
Background Nurse duty of care, the balance between nursing occupational obligations to provide care, the personal costs for providing such care, and the reward for providing care, has been significantly altered by the COVID-19 pandemic. ICU nurses are increasingly burdened with higher personal costs to fulfill their jobs, but little additional reward for continuing to provide care. Objectives The purpose of this study was to examine the impact of the COVID-19 pandemic on the duty of care balance among ICU nurses who manage COVID-19 patients. Design This was a descriptive qualitative study using semi-structured interviews. Methods Nurses were recruited for a parent study on ICU nursing during COVID-19; this is a secondary analysis of the interviews that took place during the parent study. Content analysis was utilized to identify themes from interview transcripts. Results Thirteen nurses participated in interviews. Nurses reported betrayal at perceived breeches in their duty of care agreement by their employers, the general public, and national health authorities. They described alterations to previous standards of care such as significantly increased workloads, worsening understaffing, and changes to patient care expectations that were implemented for reasons other than betterment of patient care. Nurses reported they felt a moral obligation to provide care, however they experienced disempowerment and burnout that affected them both in and out of the workplace. Conclusion The COVID-19 pandemic has affected several aspects of the duty of care balance, resulting in a duty of care balance that is inequitable to nurses. Imbalance in the effort, risks, and rewards for nursing professionals may contribute to nurse burnout. Relevance to Clinical Practice This research highlights the need for healthcare administrators to consider resource allocation, nurse appreciation, and commensurate compensation for professional nurses.